Peran Kepemimpinan Kepala Sekolah Dasar Sebagai Supervisor Dalam Meningkatkan Kompetensi Pedagogik Guru Pendidikan Agama Islam di UPTD SDN 2 Rama Puja Lampung Timur - Dili Arissandi (Journal of Creative Student Research, 2024)
Supervision is an activity of providing assistance and guidance for teachers in carrying out their duties and responsibilities. The leadership role of the Junior School head as a supervisor is very important in providing assistance and guidance as well as services to teachers including PAI teachers in improving their pedagogical competence. The leadership role of the Junior principal enables the implementation of an optimal learning process in Junior School. This is also a concern for the head of UPTDSDN 2 Raman Utara Kec. Raman Utara Lampung Timur Regency, Lampung Province in carrying out its supervisory role in order to improve the pedagogic competence of teachers, including PAI teachers so that the quality of education in the Junior School they lead can develop and excel in both academic and non-academic fields. This study discusses the "Leadership Role of Junior School Heads as Supervisors in Improving the Pedagogic Competence of PAI Teachers at UPTD SDN 2 Rama Puja Kec. Raman Utara Lampung Timur Regency Lampung Province” with the formulation of the problem: How is the Leadership Role of Junior School Heads as Supervisors in Improving the Pedagogic Competence of PAI Teachers at UPTD SDN 2 Rama Puja Kec. Raman Utara, Lampung Timur Regency, Lampung Province ?. The purpose of this study was to analyze the leadership role of the Junior School head as a supervisor in improving the pedagogic competence of PAI teachers at UPTD SDN 2 Rama Puja Kec. Raman Utara, Lampung Timur Regency, Lampung Province. The results of the analysis show that the leadership role of the Junior School head as a supervisor in improving the pedagogic competence of PAI teachers at UPTD SDN 2 Rama Puja Kec. Raman Utara Kab. Lampung Timur, Lampung Province is to create an atmosphere of teaching and learning process that meets standards or aspects of pedagogic competence so as to improve the quality of education both in quality and quantity. This is done by the Head of Junior School through assistance and guidance as well as using existing supervision techniques, thereby motivating the teacher himself in improving his pedagogical competence.